KARAKTERISTIK DAN PENERAPAN ISLAMIC CORPORATE GOVERNANCE PADA PERBANKAN SYARIAH - Fadiyah Hani Sabila (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
As one of the business entities under the umbrella of the unitary state of Indonesia, Islamic banks are also required to implement Good Corporate Governance which will henceforth be abbreviated as GCG. The application of GCG in Islamic banks is important considering Islamic banks are banks that use the principle of profit sharing. GCG is a requirement for Islamic banks to develop well and healthy. Good GCG implementation refers to five principles, namely accountability, transparency, independence, responsibility and fairness. The concept of Good Corporate Governance between conventional banks and Islamic banks is basically the same, but the difference between the two is the existence of Shariah compliance and the existence of the Sharia Supervisory Board (DPS). Islamic banks managed and owned by human resources who have integrity (good morals) and professionals, will encourage the implementation of the principles of good governance (Good Corporate Governance).